PENERAPAN PEMBELAJARAN FISIKA MENGGUNAKAN APLIKASI PHET SIMULATION UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI RANGKAIAN LISTRIK KELAS IX SMPN 4 UKUI - Wida Cahyaning Sari; Yennita Yennita; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effect of using the PhET Simulation application on learning activities so that it can improve students' cognitive physics learning outcomes. This research was conducted at SMPN 4 Ukui with the research subjects being students of class IX A and IB. The number of students in class IX A is 25 students and class IX B is 25 students. The type of research in this research is a quasi-experimental research. The data collection technique used in this study was a test by giving a posttest. The data analysis technique used in this research is descriptive analysis technique. The results obtained in this study are that the implementation can improve students' cognitive physics learning outcomes in terms of the mean, median and mode class IX A is superior to Class IX B. The average value of class IX A is 83.38 which is included in the very high category with a median value is 82.84 and modus value is 84.5 and in class IX B the average value is 68.73 which is in the high category range with media value is 66.42 and modus value is 67.5. The conclusion of this research is that there is an effect of applying the PhET Simulation application to the cognitive physics learning outcomes of SMPN 4 Ukui students, which can improve students' cognitive physics learning outcomes on electrical circuit material.Keywords: Application, PhET Simulation, Cognitive Learning Outcomes